PEMANFAATAN CANGKANG TELUR SEBAGAI PUPUK ORGANIK : EDUKASI KEPADA MASYARAKAT DESA PASAR RAWA, KABUPATEN LANGKAT - Sintia Situmorang; Titin Anisa Tanjung; Amanda Azzahra; Maulana Hasan; Tanti Jmaisyaroh Siregar (Jurnal Padamu Negeri, 2025)
Household waste management is a solution to support environmental sustainability. Eggshells, which have a high calcium carbonate content and can be used as organic fertilizer, constitute a waste that can be recovered. This article discusses the community service activities carried out in Pasar Rawa Village, Gebang District, Langkat Regency, with the aim of educating the community on how to use eggshells as organic fertilizer. This activity was carried out in three main stages, namely guidance to provide basic knowledge, direct training to practice making organic fertilizer from eggshells, and discussions to deepen understanding and answer to questions from the community. The results of the activity showed that the community was enthusiastic to participate in the training and that most participants were able to process eggshells into organic fertilizer independently. In addition to raising public awareness of the importance of waste management, this activity also has economic and environmental benefits. It is hoped that this program can be the first step towards building a culture of sustainable community waste management.